Improving Students’ Interaction And Motivation By Teachers’ Questioning Strategies - Zuraidah Nasution; Syafrina Prihatini (Universitas 17 Agustus 1945, 2022)
Question and answer is a classroom activity that allows learners to create or recreate meaning through language. Effective questioning is a means for students to respond during the learning process. Designing questions that capture student interest and attention comprises diagnosing and verifying specific facts or information, determining, and encouraging analytical, inductive, differentiation, extension, application, problem-solving, and synthesis skills. To be effective, we must design questions and answers to request information. Effective classroom questioning techniques require good preparation and do not require students to use thinking skills. This article illustrates that Q&A is a very common activity that can help students learn English and is an important way for students to exchange ideas with teachers and students. The article also covers some basic questions and examines questioning techniques in English teaching.